2013
DOI: 10.1080/09585192.2013.778318
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intentions among repatriated employees in an emerging economy: the Indian experience

Abstract: In the present global environment, liberalization of international trade and the intense international competition, it has become more important for multinational corporations (MNCs) to internationalize their business. In the course of the internationalization, it is imperative that MNCs need to offer their employees the possibility of working abroad (called expatriation). However, studies have shown that when expatriates return to the home organization, called repatriation, it is related to many problems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Further, it must be noted that in this study, the interaction between organizational repatriation support and career derailment explained the smallest amount of variance in the dependent variable. One explanation is that similar to other studies we found a significant direct effect on repatriation retention (Birur & Muthiah, 2013;Stroh, 1995). Accordingly, repatriation support increases intent to stay per se.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, it must be noted that in this study, the interaction between organizational repatriation support and career derailment explained the smallest amount of variance in the dependent variable. One explanation is that similar to other studies we found a significant direct effect on repatriation retention (Birur & Muthiah, 2013;Stroh, 1995). Accordingly, repatriation support increases intent to stay per se.…”
Section: Discussionsupporting
confidence: 90%
“…Third, this study casts new light on the role of organizational support in the repatriation context. Thus far, repatriation research primarily regards organizational repatriation support as a predictor of objective career success upon return from an IA (e.g., Bolino, 2007;Kraimer et al, 2009), or as a factor immediately contributing to the former expatriates' retention (e.g., Birur & Muthiah, 2013;Stroh, 1995). Our study somewhat supports this, because we too found a significant direct effect.…”
Section: Theoretical Contributionsupporting
confidence: 74%
“…Turnover intention issue among employees is one of the key concerns of top management as the hiring and training of new staff require more resources, time, money, knowledge, and so on [6]. One major challenge modern organizations face is turnover [7]. In this regard, keeping good and experienced staff should be a topmost priority in a much significant sector such as the power industry.…”
Section: Introductionmentioning
confidence: 99%
“…Repatriates see the home context as unfamiliar, and they need to readjust and settle into that context. Particularly, the literature on corporate repatriation has stressed the importance of effective management of repatriation and highlighted the fact that unsuccessful management of repatriation leads to employees suffering from problems of adjustment which result in stress, loss of motivation at work and turnover intention (Birur & Muthiah, 2013; Black, Gregersen & Mendenhall, 1992; Kulkarni, Lengnick-Hall & Valk, 2010; Lee & Liu, 2007). This situation leads to adverse consequences; for example, high turnover and low performance were observed among repatriates.…”
Section: Background Of the Problemmentioning
confidence: 99%